-k+5(-3k+3)=15-4K

Simple and best practice solution for -k+5(-3k+3)=15-4K equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -k+5(-3k+3)=15-4K equation:


Simplifying
-1k + 5(-3k + 3) = 15 + -4K

Reorder the terms:
-1k + 5(3 + -3k) = 15 + -4K
-1k + (3 * 5 + -3k * 5) = 15 + -4K
-1k + (15 + -15k) = 15 + -4K

Reorder the terms:
15 + -1k + -15k = 15 + -4K

Combine like terms: -1k + -15k = -16k
15 + -16k = 15 + -4K

Add '-15' to each side of the equation.
15 + -15 + -16k = 15 + -15 + -4K

Combine like terms: 15 + -15 = 0
0 + -16k = 15 + -15 + -4K
-16k = 15 + -15 + -4K

Combine like terms: 15 + -15 = 0
-16k = 0 + -4K
-16k = -4K

Solving
-16k = -4K

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Divide each side by '-16'.
k = 0.25K

Simplifying
k = 0.25K

See similar equations:

| P^3-4p^2=O | | w+2=98 | | sen4x=1/2 | | 5+14a=9a-2 | | 15+14p=2 | | 3(-4)=9 | | j-47=29 | | 2x+1+2x=96 | | (8)/(3X^2) | | -3x^2+24x=17 | | 92=x+20 | | y+2.7=18.3 | | 120n=1320 | | 39-3x=7(x+2)-5 | | A-15x=0 | | y=-0.5*2 | | 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 | | 10.44x=26.3 | | 5x(5+4)= | | CosX=-.08092 |

Equations solver categories